Field study on thermal comfort and energy saving potential in 11 split air-conditioned office buildings in Changsha, China. (1st September 2019) - Wu, Zhibin; Li, Nianping; Wargocki, Pawel; Peng, Jingqing; Li, Jingming; Cui, Haijiao
Abstract: All existing thermal comfort standards are applicable to naturally ventilated buildings and air-conditioned buildings, except mixed-mode buildings. Split air-conditioned buildings, as a type of mixed-mode buildings, account for a large proportion of current buildings. It is urgent to explore the applicability of thermal comfort standards and determine the energy saving potential in split air-conditioned buildings. In this research, the authors conducted a field study in Changsha, China. Eleven split air-conditioned office buildings were investigated from July to September 2016. 442 valid data sets were obtained. The results indicated that occupants preferred a "cooler" temperature of 26 °C, 0.6°Clower than neutral temperature of 26.7 °C. Occupants have adapted to thermal environment and accepted higher temperature than that predicted by PPD. 95% of occupants were satisfied with the thermal environment. Compared to PMV model, the adaptive model was more applicable to split air-conditioned buildings. 8.6% of cooling energy could be conserved during summer in split air-conditioned buildings. Highlights: Occupants preferred slightly cool environment. Acceptable temperature was 1.2 °C higher than that predicted by PPD. 8.6% of cooling energy could be saved during summer. Adaptive comfort model can be applied in building split air-conditioned.